Case Report: Severe brigatinib-induced pneumonitis in a patient with EML4–ALK+ metastatic non-small cell lung adenocarcinoma - Dasika, Khyati Somayaji; Melody, Megan; Patel, Jyoti D. (Frontiers in Oncology, 2025)
Anaplastic lymphoma kinase (ALK) tyrosine kinase inhibitors (TKIs), such as brigatinib, are targeted therapies for metastatic non-small cell lung cancer (mNSCLC). We present a patient with echinoderm microtubule-associated protein-like 4 (EML4) and ALK fusion protein-positive mNSCLC who developed severe hypoxemia and pneumonitis requiring intubation within 2 days of initiating brigatinib therapy. The workup for alternative etiologies of respiratory distress was unrevealing, and the patient was treated for presumed brigatinib-induced pneumonitis with high-dose methylprednisolone. This case demonstrates high-grade, rapidly progressive brigatinib-induced pneumonitis with prompt clinical improvement after steroids and a marked disease response without recurring toxicity after treatment with an alternative ALK TKI, alectinib.